HUBUNGAN ANTARA DEPRESI DENGAN INSOMNIA PADA LANSIA DI UPTD PANTI SOSIAL TRESNA WERDHA NIRWANA PURI SAMARINDA - Milkhatun Milkhatun (Jurnal Ilmu Kesehatan, 2017)
Background: The large number of elderly people has consequences for both phsycal and psychosocial aspect of life. The next problem was experienced by elderly is the decreasing of health condition, retreat of physical ability, the decreasing of mental condition, unfunctioning of potency, abandoned, no work, no life stock and unsustainable condition of support. This situation can lead to elderly often experience which further leads to sleep disorder such as insomnia.Purpose: The aim of this research is to identifying the correlation between depression and insomnia on elderly in the Tresna Werdha Nirwana Puri Nursing Home Samarinda 2017. Methode: This research used a descriptive correlation design with cross sectional approach. The population of this research were 111 elderly. With stratified random sampling technique obtained 53 respondents. The data was collected through questionnaires and was analyzed with Spearman Rank test (rho).Results: The result of Spearman Ranks (Rho) test showed correlation coefficient value of 0,557 with medium correlation strength and significance level 0.000 (a <0,05).Conclusion: There is a significant correlation between depression and insomnia on elderly people in Tresna Werdha Nirwana Puri Nursing Home Samarinda 2017.Suggestions: For Elderly in the Tresna Werdha Nirwana Puri Nursing Home Samarinda, they are suggested to more doing activities like a physical activites,religion activities, and always think positively to reduce the level of depression and insomnia.